Combining biopsy tools improves mutation detection rate in central lung cancer. Issue 3 (14th September 2020) - Hagmeyer, Lars; Schäfer, Stephan; Engels, Marianne; Fassunke, Jana; Pietzke-Calcagnile, Anja; Treml, Marcel; Herkenrath, Simon-Dominik; Matthes, Sandhya; Wolf, Jürgen; Büttner, Reinhard; Randerath, Winfried
Molecular genetic testing (such as next-generation sequencing (NGS)) and programmed death ligand 1 (PD-L1) staining have become essential for the evaluation of lung cancer tissue [1, 2]. Endobronchial forceps biopsy (FB) is considered the gold standard for tissue sampling in central lung cancer [3]. In central exophytic lung cancer, the detection rate of oncogenic mutations and PDL1 positivity may be increased by combined sampling by forceps and EBUS-TBNA. The additional sampling of mediastinal lymph node and ctDNA may not be of additional benefit. https://bit.ly/2Ve41EF